Numerical simulation of mass transfer and fluid flow evolution of a rectangular free jet of air - Di Venuta, Ivan; Petracci, Ivano; Angelino, Matteo; Boghi, Andrea; Gori, Fabio (Elsevier, 2017)
The paper presents Large Eddy Simulations (LES) of mass transfer and fluid flow evolutions of a submerged rectangular free jet of air in the range of Reynolds numbers from Re = 3400 to Re = 22,000, with the Reynolds number, Re, defined with the hydraulic diameter of the rectangular slot, of height H. The numerical simulations are 3D for Re = 3400 and 6800, while 2D for Re = 10,400 and 22,000 to reduce computational time costs. The average and instant LES numerical simulations are compared with the concentration visualizations, obtained with the Particle Image Velocimetry (PIV) technique, and the fluid dynamics variables, velocity and turbulence, measured with the PIV technique and the Hot Film Anemometry (HFA). In the numerical simulations, the Schmidt number is equal to 100 to compare the air concentration in the PIV experiments, while the turbulence on the exit of the slot is equal to the value measured experimentally, and ranging between 1% and 2%. The average 2-3D LES simulations are in agreement with the concentration and the fluid dynamics experimental results in the Undisturbed Region of Flow (URF) and in the Potential Core Region (PCR), while the vortex breakdown is captured only by the 3D LES approach. As far as the instant flow evolution is concerned, the 2-3D LES simulations reproduce the Negligible Disturbances Flow (NDF), where the jet height maintains constant, and the Small Disturbances Flow (SDF), where the jet height oscillates, with contractions and enlargements, but without the vortex formation. Average and instant velocity and turbulence numerical simulations on the centreline are in good agreement to the experimental PIV measurements.
Keywords: 2-3D Large Eddy Simulations; Transitional to turbulent flow; Numerical concentration and velocity fields compared to PIV visualizations; Numerical fluid dynamics variables compared to HFA measurements; Confirm of URF in average flow and NDF; SDF in instant flow